Analisis Biochemical Oxygen Demand (BOD) sebagai Indikator Kualitas Air Limbah Rumah Sakit Menggunakan Metode Winkler - Inggrid Dwi Gusprizal; Jon Efendi (Lembaga Yasin AlSys, 2026)
Hospital wastewater contains organic matter, pathogenic microorganisms, and various chemical compounds that may pollute the environment if not adequately treated. One important parameter for evaluating the organic matter content of wastewater is biochemical oxygen demand (BOD). This study aimed to evaluate the wastewater quality of several hospitals based on the BOD parameter using the Winkler method in accordance with SNI 6989.72:2009. The study employed a quantitative descriptive approach through laboratory analysis of wastewater samples from several hospitals. Testing was conducted by measuring dissolved oxygen (DO) concentrations before and after five days of incubation, calculating BOD values, and evaluating the precision of the measurement results using relative percent difference (RPD). The results showed that the mean BOD values ranged from 1.9328 to 3.2858 mg/L, while the RPD values for all samples ranged from 7% to 23%. Differences in BOD values among samples indicated variations in wastewater characteristics associated with healthcare service activities and treatment effectiveness at the wastewater treatment plant (WWTP) of each hospital. All samples had relatively low BOD values, indicating that the biodegradable organic matter content had decreased after the treatment process. The RPD values also showed that the analytical results had good precision and could therefore be used as a basis for monitoring hospital wastewater quality. These findings emphasize the importance of BOD as an indicator of wastewater quality and the effectiveness of biological treatment at hospital WWTPs. Keywords: Hospital Wastewater; Biochemical Oxygen Demand; Water Quality; Winkler Method; Wastewater Treatment